EFFECT OF COMPENSATION POLICY ON NON-PERFORMING LOANS IN MICROFINANCE BANKS IN ABUJA (ABUJA JOURNAL OF BUSINESS AND MANAGEMENT, 2025)
The study examined the effects of compensation policy on non-performing loans in Microfinance banks in Abuja. Specifically, the study assessed the effects of compensation variables on microfinance banks non-performing loans. To achieve this, the study through stratified sampling method chose fourteen microfinance banks that were state categories and two hundred and sixty staff members bifurcated into management and non-management. The study adopted survey research design. The population of the study in the chosen microfinance banks consists of 411 staff. This is made up of 78 (19%) management staff and 333(81%) middle level staff. The research adopted both quantitative and qualitative approach to analyse the results of the study. The quantitative data was collected through primary survey likert-scale questionnaire that was administered to 360 staff of the chosen microfinance banks. SPSS-20 was used to analyse the data collected in which simple percentage, correlation, ordinary least square regression analyses and ANOVA were used. Analysis of findings revealed that in compensation policies, direct compensation has a positive and significant relationship with non-performing loans, variable pay has a positive and significant relationship with non-performing loans and medical reimbursable allowance has positive and insignificant effect on non-performing loans in microfinance banks in Abuja. The study recommended that Microfinance banks in Abuja should continue to use compensation policies to checkmate Non-performing loans in the banks and in addition, they should effectively use house rent allowance, profit sharing allowance and minimise the use of medical reimbursement allowance, but should strongly utilize variable pay.